STRATEGI CORPORATE SOSIAL RESPONSIBILITY (CSR) PERUSAHAAN TJIWI KIMIA DALAM SISTEM MANAJEMEN BERORIENTASI PADA SUSTAINABILITY ENVIRONMENT - HERAWATI, INGGAR (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTThis research analyze about CSR activity in the Tjiwi Kimia companies. The purpose of this research is to know effect CSR for the environment and the benefit for the company. The method of the analysis are using the descriptive qualitative. Data are processed in this study were obtained from the results of questionnaires to community in Tjiwi Kimia company. Based on the research result showed that the Tjiwi Kimia Company have good CSR program, a have positive impact on the environment and Tjiwi Kimia gets image as good corporate.Keywords: CSR, PT Tjiwi Kimia, Sustainability Environment